Hypofractionated carbon ion therapy delivered with scanned ion beams for patients with hepatocellular carcinoma: feasibility and clinical response - Habermehl, Daniel; Debus, Jürgen; Ganten, Tom M.; Ganten, Maria-Katharina; Bauer, Julia; Brecht, Ingo; Brons, Stephan; Haberer, Thomas; Härtig, Martin; Jäkel, Oliver; Parodi, Katia; Welzel, Thomas; et al. (Radiation oncology, 2013)
Photon-based radiation therapy does currently not play a major role as local ablative treatment for hepatocellular carcinoma (HCC). Carbon ions offer distinct physical and biological advantages. Due to their inverted dose profile and the high local dose deposition within the Bragg peak, precise dose application and sparing of normal tissue is possible. Furthermore, carbon ions have an increased relative biological effectiveness (RBE) compared to photons.